Tarihte Müzisyen Şahsiyetler: İbnü’t-Tahhân’ın Hâvi’l-Fünûn ve Selvetü’l-Mahzûn Adlı Eseri Üzerine Bir İnceleme - Sevinç, Muhammet; Turabi, Ahmet Hakkı (Journal of History Culture and Art Research, 2020)
Musician Figures in History: A Study on Hawi al-Funun wa-Salwat al-Mahzun of Ibn al-Tahhan Abstract Hawi al-Funun wa-Salwat al-Mahzun was written by Ibn al-Tahhan who was one of the palace musicians in Egypt (Fatimids period) between X-XI centuries. According to the available sources, it is the only known musical work that has survived since the Fatimids period. This work, written by a professional musician, consists of two main articles dealing with the scientific and practical aspects of the music art and has an encyclopedic feature with a hundred and two subject titles. One of the most important features that distinguishes Hawi al-Funun wa-Salwat al-Mahzun among early music sources is that the work sheds light on the music of the Fatimids period, as well as the seven hundred musicians who lived between the Jahiliyya period and the Fatimids period. This study, firstly, gives information about Ibn al-Tahhan and his famous study Hawi al-Funun wa-Salwat al-Mahzun, and secondly, as mentioned by Ibn al-Tahhan, gives information about the famous musicians who lived between the period of jahiliyyah and the Fatimids period. Tarihte Müzisyen Şahsiyetler: İbnü’t-Tahhân’ın Hâvi’l-Fünûn ve Selvetü’l-Mahzûn Adlı Eseri Üzerine Bir İnceleme Öz Hâvi’l-Fünûn ve Selvetü’l-Mahzûn adlı eser, X-XI. asırlar arasında Mısır’da (Fâtımîler dönemi), saray müzisyenlerinden olan İbnü’t-Tahhân tarafından kaleme alınmış olup eldeki kaynaklara göre Fâtımîler döneminden günümüze ulaşabilmiş bilinen tek mûsikî eseridir. Profesyonel bir müzisyen tarafından kaleme alınan bu eser, mûsikî sanatının ilmi ve ameli yönlerinin ele alındığı iki bölümden oluşmakta ve içerisinde yer alan yüz iki konu başlığı ile ansiklopedik bir özellik taşımaktadır. Erken dönem mûsikî kaynakları arasında Hâvi’l-Fünûn ve Selvetü’l-Mahzûn’u farklı kılan en önemli özelliklerinden birisi, eserin Fâtımîler dönemi mûsikî kültürüne ışık tutmasının yanı sıra, eserde cahiliye dönemi ile müellifin yaşadığı Fâtımîler dönemi arasında yaşamış beş yüze yakın mûsikîşinasın isimlerinin tasnifli bir şekilde zikredilmesidir. Bu çalışmada öncelikle İbnü’t-Tahhân ve Hâvi’l-Fünûn ve Selvetü’l-Mahzûn adlı eseri tanıtılacaktır. Ardından da eserde adı geçen, cahiliye dönemi ile müellifin yaşadığı Fâtımîler dönemi arasında yaşamış müzisyenler hakkında bilgi verilecektir.